Super-resolution radially polarized pupil-filtering confocal Raman spectroscopy technology. (27th December 2019) - Li, Shucheng; Qiu, Lirong; Wang, Yun; Cui, Han; Zhao, Weiqian
Abstract: The spatial resolution of traditional confocal Raman spectroscopy cannot overcome the diffraction limit, which limits its application as a high-spatial-resolution technique. In this paper, a super-resolution radially polarized pupil-filtering confocal Raman spectroscopy (SRPCRS) method is proposed to solve this problem. This method combines confocal Raman spectroscopy imaging technology with radially polarized light compact-focusing technology. The spatial resolution of confocal Raman spectroscopy imaging can be improved by compressing the diameter of the incident spot and by image restoration technology. Simulation and experimental analyses show that this method can increase the spatial resolution of the confocal Raman spectroscopy system to 160 nm when the laser wavelength is 532 nm and the objective lens has an NA of 0.9. This method provides an effective way to achieve high-spatial-resolution confocal Raman spectroscopy images.